KELAYAKAN MULTIMEDIA PEMBELAJARAN INTERAKTIF DALAM MEMOTIVASI SISWA BELAJAR MATEMATIKA - Lilis Diah Kusumawati; nFn Sugito; Ali Mustadi (Kwangsan: Jurnal Teknologi Pendidikan, 2021)
Interactive multimedia is a technology that mediates the development of learning activities to make it more interesting and enjoyable so that it can motivate students to learn. This study aims to determine feasibility of interactive learning multimedia product in motivating student for fourth grade of elementary school to learn mathematics. The research method uses the concept of ADDIE models to develop products with five stages, 1) analyze; 2) design; 3) develop; 4) implement; and 5) evaluate. The result showed that the development of interactive learning multimedia is feasible used for motivating students in grade 4 to learn mathematics. The result of validation by material experts showed that the products developed reached a score of 43 so that it was included in the "very good" category, while the results of the validation by the media experts showed that the products developed reached a score of 59 so that it was included in the "very good" category. Teacher responses related to the practicality of product use reached a score of 113 so that it was included in the "very good" category, while student responses related to the practicality of using the product reached a score of 83 so that it was included in the "very good" category. In motivating students to learn mathematics, interactive learning multimedia can be applied to elementary school students in grade 4. AbstrakMultimedia interaktif adalah teknologi yang memediasi pengembangan kegiatan pembelajaran agar lebih menarik dan menyenangkan sehingga mampu memotivasi siswa dalam belajar. Penelitian ini bertujuan untuk mengetahui kelayakan produk multimedia pembelajaran interaktif dalam memotivasi siswa kelas IV sekolah dasar untuk belajar matematika. Metode penelitian menggunakan konsep model ADDIE untuk mengembangkan produk dengan lima tahap, 1) menganalisis; 2) desain; 3) berkembang; 4) mengimplementasikan; dan 5) mengevaluasi. Hasil penelitian menunjukkan bahwa pengembangan multimedia pembelajaran interaktif layak digunakan untuk memotivasi siswa kelas 4 dalam belajar matematika. Hasil validasi oleh ahli materi menunjukkan bahwa produk yang dikembangkan mencapai skor 43 sehingga masuk dalam kategori “sangat baik”, sedangkan hasil validasi oleh ahli media menunjukkan bahwa produk yang dikembangkan mencapai skor 59 sehingga masuk dalam kategori "sangat baik". Tanggapan guru terkait dengan kepraktisan penggunaan produk mencapai skor 113 sehingga masuk dalam kategori “sangat baik”, sedangkan respons siswa terkait dengan kepraktisan penggunaan produk mencapai skor 83 sehingga masuk dalam kategori “sangat baik”. Dalam memotivasi siswa untuk belajar matematika, multimedia pembelajaran interaktif dapat diterapkan untuk siswa sekolah dasar di kelas 4.